Return, Volatility, and Volume : Causality Relationship of Top 10 Companies of Nifty 50 - Nandan, Tanuj; Agrawal, Pravin Kumar; Agarwal, Tanu (Indian Journal of Research in Capital Markets, 2016)
The present paper dealt with the short-run causal relationship between stock returns, stock price volatility, and trading volume of top 10 companies of the National Stock Exchange. Granger causality test was applied to the data taken on a quarterly basis from 2008-09 to 2014-15. The study found bi-directional relationship between stock returns and trading volume of HDFC Bank and TCS, that is, trading volume was found to reinforce stock returns and returns to reinforce trading volume. Again, in case of Reliance Industries, bi-directional or two way causal relationships were found between stock return and volatility. There was uni-directional or one way causality relationship in case of stock returns and trading volume of Infosys and Reliance, which means returns Granger cause trading volume, but this does not apply the other way around. This implies that there is an indication of noise trading model of interaction between stock returns and trading volume in these stocks.